AGRESIVITAS PAJAK TERHADAP NILAI PERUSAHAAN DENGAN LEVERAGE PADA PERUSAHAAN PERTAMBANGAN - Dwi Nita Aryani; Rahmat Fauzi (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2023)
This study aims to analyze the influence of Tax Aggressiveness on firm value with Leverage as an Intervening variable, in Mining Sector Companies listed on the Indonesia Stock Exchange. The research method used is descriptive correlational quantitative method. The sampling technique was carried out by purposive sampling method, and obtained a sample size of 10 mining companies listed on the Indonesia Stock Exchange, on period of 2017-2021. The data analysis used in this research is partial least square. Statistical test results show that the Effective Tax Rate has a positive relationship with the Debt to Equity , which means that the more aggressive the company towards taxes, the higher the leverage, while the Leverage has a negative effect with firm value. Tax aggressiveness directly to firm value proved to have no effect, but the indirect effect of tax aggressiveness to firm value through leverage proved significant value and showed an inverse relationship, so it can be concluded that the higher the tax aggressiveness, the higher the leverage, and the lower the firm value.